Community Structure of Ascidian in Mike’s Point Bunaken Waters, Manado City, North Sulawesi Province - Samuel L. Opa; Deiske A. Sumilat; Silvester B. Pratasik; Billy Th. Wagey; Gustaf F. Mamangkey; Elvy L. Ginting; Medy Ompi (Sam Ratulangi University, 2020)
Ascidians are marine invertebrates that have been classified with the subphylum Urochordata (Tunicata). These organisms are very important because they contribute a lot to the stability of the marine ecosystem. This study aims to determine the species composition, density, ecological index (diversity, uniformity, dominance), distribution patterns, and substrate occupied by Ascidian. Data were collected at Mike’s Point Bunaken waters at two depths 7 m and 14 m. The method used a direct observation along the 50 m and 2 m width belt transect. In this study, the transect was applied parallel to the coastline at each depth, where 3 replications were performed. The results show 26 species consisting of 13 species at a depth of 7 m and 22 species at a depth of 14 m were identified. The average density of each species was 0.05 ind/m2 at both depths. Diversity Index of 1.76 at 7 m depth and 2.24 at 14 m depth was determined. Uniformity Index was 0.68 at 7 m depth and 0.73 at 14 m depth. Dominant Index of 0.67 at 7 m depth and 0.88 at 14 m depth was also determined. The distribution pattern of species was dominated by uniform distribution, and the substrate most commonly occupied by Ascidianns was dead coral overgrown with algae.Keywords: Ascidian, composition and density, ecological index, distribution pattern, substrate AbstrakAscidian adalah Avertebrata laut yang termasuk dalam subfilum Urochordata (Tunicata). Organisme ini sangat penting karena mereka banyak berkontribusi pada stabilitas ekosistem laut. Penelitian ini bertujuan untuk menentukan komposisi spesies, kepadatan, indeks ekologi (keanekaragaman, keseragaman, dominasi), pola distribusi, dan substrat yang ditempati oleh Ascidian. Data dikumpulkan di Perairan Mike's Point Bunaken pada dua kedalaman 7 m dan 14 m. Metode yang digunakan adalah pengamatan langsung sepanjang transek sabuk 50 m dan lebar 2 m. Transek dipasang sejajar dengan garis pantai dan pada setiap kedalaman. Pengambilan data dilakukan 3 ulangan. Hasil dari penelitian ini adalah ditemukan 26 spesies yang terdiri dari 13 spesies pada kedalaman 7 m dan 22 spesies pada kedalaman 14 m. Kepadatan total Ascidian pada kedalaman 7 m (0,67 ind/m2) dan pada kedalaman 14 m (1.11 ind/m2). Indeks Keanekaragaman adalah 1,76 pada kedalaman 7 m dan 2,24 pada kedalaman 14 m. Indeks Keseragaman adalah 0,68 pada kedalaman 7 m dan 0,73 pada kedalaman 14 m. Indeks Dominansi 0,67 pada kedalaman 7 m dan 0,88 pada kedalaman 14 m. Pola distribusi spesies didominasi oleh pola distribusi yang seragam, dan substrat yang paling umum ditempati oleh Ascidian adalah karang mati yang ditumbuhi alga.Kata Kunci: Ascidian, komposisi dan kepadatan, indeks ekologi, pola sebaran, substrat